Phytochemical Analysis and Chymotrypsin Inhibitory Potential of Galium sp. and Solidago sp. via Effect-Directed HPTLC Bioassay - Bartosz Rył; Izabela Jasicka-Misiak (Molecules)
Chymotrypsin inhibitors were initially considered mainly as anti-nutritional factors. However, the potential for their use as therapeutics has been recognized, particularly in the control of cancer, neurodegenerative diseases, and inflammatory processes. The search for new, effective, and safe chymotrypsin inhibitors has become important not only for food and feed safety reasons, but also in the search for new compounds with potential for use in the pharmaceutical industry. Oxidative stress is also an integral etiological factor in the development of the aforementioned pathological conditions. Antioxidants supplied with food can have an impact on reducing the probability of developing these diseases. Herbaceous plants are a valuable reservoir of biologically active chemical compounds, which can show both inhibitory effects against a number of enzymatic reactions and have antioxidant activity. The compounds found within them are also often characterized by higher bioavailability and safety than their synthetic analogs. In the present study, phytochemical characterization of plant materials Galium aparine L., Galium verum L., Solidago virgaurea L. and Solidago canadensis L. was performed, in order to search for new, potential substances with chymotrypsin inhibitor and antioxidant properties. Antioxidant and inhibitory activities against chymotrypsin were determined using effect-directed HPTLC. The total content of phenolic compounds and flavonoids and antioxidant activity were also determined in UV-Vis spectrophotometric tests. Both plant species showed antioxidant and chymotrypsin inhibitory activity. Among the methanol and methanol:water extracts, the extracts from Solidago sp. showed stronger inhibitory and antioxidant activity. However, in the case of dichloromethane extracts, Galium aparine inhibited chymotrypsin activity in a stronger manner than Solidago sp. The results indicate the application potential of compounds obtained from these plants as chymotrypsin inhibitors and antioxidant agents.